Prevalence and predictors of diabetes and cardiometabolic risk among construction workers in Ireland: The Construction Workers Health Trust screening study. (July 2013) - Thabit, Hood; Burns, Nicole; Shah, Shabahat; Brema, Imad; Crowley, Vivion; Finnegan, Fran; Daly, Brian; Nolan, John J
Construction workers (CW) are at increased risk for a range of chronic diseases. We screened 983 CW for diabetes and cardiometabolic risk. The age range was 18–64 years, with mean age of 36.3 years. Self-reported questionnaires, Finnish diabetes risk score and fasting blood tests were collected at the workplace. The unadjusted prevalence of pre-diabetes and type 2 diabetes mellitus were 3.6% and 1.2%, respectively; 21% of CW had the metabolic syndrome (MetS). The majority were either overweight (48.3%) or obese (21.8%). In a regression model, age remained the strongest predictor of fasting glucose ( p < 0.001). Pre-diabetes and diabetes mellitus were significantly associated with presence of the MetS [odds ratio (OR) 5.6; 95% confidence interval (CI): 2.8–11.5, p < 0.001 and OR 5.5; 95% CI: 1.6–18.7, p = 0.006, respectively]. Subjects engaged in greater physical activity outside of work had lower body mass index (26.9 vs. 28.8 kg/m 2, p = 0.03), waist circumference (95.8 vs. 98.1 cm, p = 0.03) and fasting serum triglycerides (1.1 vs. 1.4 mmol/L, p = 0.03) compared to those who were sedentary. Despite their youth and a physically demanding occupation, CW are at risk of cardiometabolic diseases. This risk increases with age and the MetS. Screening tools may be useful to identify those who are at risk.